Community Based Planned Intervention Targeting Perceptions, Attitudes and Health Seeking Behaviour Regarding Cancers in New Delhi: The Study Protocol - Tulika Seth; Atul Kotwal; Rakesh Thakur; GK Rath; DN Sharma; Jitendra Nagpal (Medsci Publications, 2019)
Background: In view of the increasing burden of cancers in devel- oping countries and this study was conducted to first understand community needs and perceptions, secondly to design and im- plement evidence based preventive strategies, and lastly to test the short-term outcome of these strategies in the field. Study Design: Cross Sectional mixed methods before and after in- tervention community based study. The study had three phases. Phase I involved understanding perceptions, attitudes and prac- tices and needs assessment using qualitative and quantitative methods, gaining from the strengths of both by combining the ap- proaches. Based on the findings of Phase I, appropriate compre- hensive interventions were designed and implemented in Phase II. A repeat survey using quantitative methodology was conducted to assess the short-term impact of the intervention. The primary out- come was change in perceptions, attitudes and contextual health care seeking practices among the community. Results: Results of this study will be reported in peer-reviewed publications and in conference presentations Conclusion: This first of its kind study in India has helped in un- derstanding the determinants of perceptions, attitude and prac- tices regarding cancer in the community, which helped in formu- lating need based intervention strategies. Testing the short-term outcome of intervention showed it to be effective. The study will help in policy decision making by the planners and administrators of the state.